ANALISIS PENENTUAN GAJI UKM XYZ MENGGUNAKAN METODE ECKENRODE - Almasah Ulya Ramadhani; Angel Mauledya Sinaga; Devita Indriana Sari; Risma Hermila Noersyafitri Fatma; Lindawati Kartika (Jurnal Pijar, 2023)
UKM XYZ does not yet have a wage structure and scale for its employees. The wage structure and scale must be owned by every entrepreneur. This is stated in the Regulation of the Minister of Manpower of the Republic of Indonesia Number 1 of 2017 concerning Wage Structure and Scale. This study aims to develop the structure and scale of wages in XYZ SMEs. This study uses the Eckenrode weighting method with 10 compensation factors which are suitable for use in determining compensation. The data used are primary data relating to compensation factors, compensation sub-factors, the weight assessment of each sub-factor, as well as each employee's assessment of the sub-factors obtained through interviews and discussions with the owner. Secondary data is in the form of supporting data obtained through scientific articles that are related to the research topic. In this study, there are 3 main criteria that refer to the Hay System position evaluation method, namely knowledge, problem solving, and accountability. Based on the weighting calculation that has been done, the results of the weight and priority level for each compensation factor are obtained. UKM XYZ has 47 employees with a total salary of IDR 97,350,000. By using this Eckenrode weighting method, there is an increase in the percentage of salaries in UKM XYZ by 24% or around IDR 24,145,120. So that the total salary of its employees reaches IDR 121,495,120.